Analisis Kesinambungan Transaksi Berjalan Indonesia: 1980 - 2010 - Handoko, Rudi (Jurnal Kajian Ekonomi dan Keuangan, 2011)
This paper attempt to analyze the sustainability of current account in Indonesia. Sustainability analysis of current account is conducted by analysing factors affecting the sustainability of current account for some particular periods. The factors affecting current account sustainability include external debt, debt service ratio, export, real exchange rate, domestic saving and investment, fiscal surplus deficit, economy growth, and capital inflow. The result shows that during period of 1980-2010 current account sustainability facing some disturbances indicated by some factors affecting current account sustainability are lying above the warning level.